An analysis of the classical and contemporary juristic opinions on bay Al- Dayn - Hanudin Amin (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2007)
The term, bay al-Dayn, has created an interest amongst the Muslim jurists of classical and contemporary alike. This issue has also driven the force to recognize the importance of bay al-Dayn pertaining to its meaning, priorities and applications in the banking industry today. Compliance to or otherwise to the principles of Shariah is the agenda of this paper entitled “An Analysis of the Classical and Contemporary Juristic Opinions on bay al-Dayn” which speaks for itself. Some issues will be analyzed in detail, and some issues will be discussed in general. Further observations and critical opinions will be offered when necessary.